Florida Homeowner Herbicide Guide: Considerations, Applications, and Selection - Chris Marble (EDIS)
While some people opt for professional lawn maintenance companies, some homeowners may wish to perform their own landscape pest control in order to save money, to have more control of what is applied, or simply because they enjoy it. This EDIS publication is for Florida gardeners, horticulturalists and homeowners who want to utilize herbicides to control weeds in their landscape. This publication discusses common herbicides available at retail stores and how homeowners can use these them safely and effectively. https://edis.ifas.ufl.edu/ep575